Experimental investigations and comparison of energy and exergy efficiencies of the box type and solar parabolic cooker - Rathore N.; Shukla S.K. (My University, 2025)
In this paper two different types of solar cookers namely simple box-type and parabolic solar cooker with its focus inside cooker, is investigated experimentally. Experiments were done at roof top of Renewable Energy Lab, Department of Mechanical Engineering, Institute of Technology, Banaras Hindu University (BHU), Varanasi, India. For comparison, these two cookers were kept on a single platform to ensure the same solar conditions. The first cooker is flat plate box type solar cooker (SBC) made of steel. The second cooker namely solar parabolic cooker (SPC) consists of acrylic mirror sheet with reflectivity of 0.75. The energy and exergy efficiencies of both the cookers were experimentally evaluated and found similar to previous studies. Copyright © 2009, Inderscience Publishers.